SNOT‐22 in a control population. (9th June 2016) - Erskine, S.E.; Hopkins, C.; Clark, A.; Anari, S.; Kumar, N.; Robertson, A.; Sunkaraneni, S.; Wilson, J.A.; Carrie, S.; Kara, N.; Ray, J.; Smith, R.; et al.
Abstract : Objectives: To assess SNOT‐22 and its subscales in a non‐rhinosinusitis UK‐wide population. Design: Self‐reported questionnaire. Setting: Based from 30 ENT departments around the UK. Participants: 250 Non‐rhinosinusitis adults – no self‐reported nasal problems in the past, no chronic conditions undergoing active treatment and no hospital admissions in the preceding 12 months. Main outcome measures: SNOT‐22, SF‐36. Results: The mean SNOT‐22 total score overall was 12.0. The mean was 10.2 for males with a median of 6.5 and a mean of 13.2 for females with a median of 9. Females scored significantly more highly than males on the sleep/fatigue and facial domains. Conclusions: Our data demonstrate differences in SNOT‐22 amongst males and females. These data can be used in future studies for comparison with different disease populations with rhinosinusitis.